Ways of Financing Innovation of Trade Business - T. I. Berg (Вестник Российского экономического университета имени Г. В. Плеханова)
The sphere of trade is on the threshold of serious changes, which take place because of growth and fluctuation in demand, globalization of commodity markets, impact of digital technologies and penetration of innovation into business-processes. E-trade is developing continuously and the number of its tools is growing extremely fast, which provides opportunities for new business-lines and projects. The development of competitive environment adjusted to new fast-growing and changing conditions of digital transformation is required. Responding to this challenge depends on introduction of advanced technical and software means, innovation, which could support business-processes at all stages of product movement. The article deals with theoretical and methodological aspects of financing trade business innovation. Types of innovation and their interconnection with business-processes are studied. The author’s matrix of finance methods was designed depending on the type of innovation and finance sources. As an alternative the authors put forward crowd-funding as a fast, cheap and low-risk method of finance support. Optimal, stable, aggressive models of innovation financing in trade were proposed, as well as the structure of ways of raising funds. The choice of finance model is based on criteria of risk factor and reserve of finance stability, which could help maneuver sources of funds depending on changing conditions of trade business entity.